Grazing Evaluation of Annual and Perennial Cool‐Season Forage Systems for Stocker Production in the Lower Transition Zone. Issue 1 (13th February 2017) - Mckee, Robert W.; Tucker, Jennifer J.; Mullenix, M. Kimberly; Prevatt, Christopher; van Santen, Edzard
Abstract : Core Ideas: A simultaneous grazing evaluation of perennial and annual cool‐season forages was conducted in the Southeast. A real‐world evaluation used production practices common in the lower transition zone. Cool‐season forages can meet stocker nutritional needs and provide high‐quality forage for grazing. Novel endophyte tall fescue has greater long‐term profit potential compared with these annual forages. Cool‐season forages provide high‐quality forage throughout the cooler months, which can reduce winter feed and hay consumption by extending the grazing season in the Southeast. Limited research has been conducted to simultaneously evaluate common annual and perennial cool‐season forage options during this time period. A 2‐year grazing trial was conducted to evaluate annual ryegrass ( Lolium multiflorum L.), mixtures of cereal rye ( Secale cereal L.) and annual ryegrass, and novel endophyte tall fescue [ Lolium arundinaceum (Shreb.) Darbysh.] seeded with annual crimson clover ( Trifolium incarnatum L.), perennial white clover ( Trifolium repens L.), or treated with spring‐applied N fertilizer. Parameters evaluated were timing and length of grazing season, forage nutritive value, forage dry matter (DM) availability, animal performance, and economic returns. Economic analysis evaluated monetary returns per acre. In Year 1 (2013–2014) annual treatments provided 68 days of grazing while perennial treatments provided 75 days. In Year 2 (2014–2015) mixtures of cereal rye and annual ryegrass provided 57 days, while annual ryegrass and novel endophyte tall fescue treatments provided 85 and 84 days, respectively. Animal average daily gain (ADG) and body weight (BW) gain/acre was greatest for ryegrass and tall fescue and least in treatments containing cereal rye. No differences in animal performance were observed between legume and N fertilizer within forage base. Novel endophyte tall fescue treatments had positive returns per acre compared with negative returns for annual treatments. These results indicate that under conditions of similar animal performance and forage production, novel endophyte tall fescue systems may provide a more economical option for producers in the lower transition zone of the Southeast.